2004
DOI: 10.1038/sj.gt.3302348
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus vector-mediated interleukin-10 gene transfer inhibits atherosclerosis in apolipoprotein E-deficient mice

Abstract: Inflammation is a major contributor to atherosclerosis by its effects on arterial wall biology and lipoprotein metabolism. Interleukin-10 (IL-10) is an anti-inflammatory cytokine that may modulate the atherosclerotic disease process. We investigated the effects of adeno-associated virus (AAV) vector-mediated gene transfer of IL-10 on atherogenesis in apolipoprotein E (ApoE)-deficient mice. A murine myoblast cell line, C2C12, transduced with AAV encoding murine IL-10 (AAV2-mIL10) secreted substantial amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 34 publications
7
66
0
1
Order By: Relevance
“…[3][4][5] In contrast, the AAV vector used in this study achieved PGIS expression with a single intramuscular injection, and this expression was sustained for 1 year. 7 Furthermore, gene transfer was believed to be safer when performed via an intramuscular approach as opposed to the intratracheal or intrahepatic approaches. 6 Currently, researchers are using adenoviral gene transfer in most clinical trials because of its high efficiency for gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] In contrast, the AAV vector used in this study achieved PGIS expression with a single intramuscular injection, and this expression was sustained for 1 year. 7 Furthermore, gene transfer was believed to be safer when performed via an intramuscular approach as opposed to the intratracheal or intrahepatic approaches. 6 Currently, researchers are using adenoviral gene transfer in most clinical trials because of its high efficiency for gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…We reported previously that a stable serum concentration of a secretory protein was achieved over a 1-year period by using a single intramuscular injection of several AAV vector (AAV2 and AAV5) serotypes in mice. 7 Currently, AAV1 is one of the most efficient serotypes for muscle transduction. 8,9 Single subcutaneous injection of a pyrrolizidine alkaloid, namely, monocrotaline (MCT), produces severe PAH and PA remodeling in rats.…”
mentioning
confidence: 99%
“…For example, general immune suppressors interleukin-10 and tumor growth factor-b1 have been shown to inhibit atherosclerosis in mouse models. [8][9][10][11] The manipulation of the immune system may be achieved through cytokines or other genes that selectively inhibit T-helper cell type 1 response or other arms of the immune system, or to increase CD4(+), CD25(+) regulatory T cells (Tregs). 12,13 Atherogenesis has also been inhibited by altering lipid transport by the delivery of apolipoprotein E or apolipoprotein A1 Milano.…”
Section: Introductionmentioning
confidence: 99%
“…7 The decreased levels of glucose and triglyceride that appeared in the control group may be associated with malnutrition after stroke episodes. Decreased serum albumin levels in this group might result from proteinuria caused by hypertensive renal dysfunction.…”
Section: Il-10 Prevents End-organ Damage In Shr-sp T Nomoto Et Almentioning
confidence: 94%
“…[4][5][6] We also reported that in ApoE-deficient mice, a single intramuscular adenoassociated virus (AAV) vector injection resulted in sustained IL-10 expression for over 6 months and improved atherosclerosis. 7 Several evidences suggest that IL-10 regulates endothelial NOS, endothelin-I and heme oxygenase-1 that substantially associate with blood pressure and vascular remodeling of resistance artery in a genetic model of hypertension. Although the overall contribution of inflammation to vascular damage in patients with hypertension remains to be clarified, several forms of experimental hypertension have been used to demonstrate monocyte/macrophage infiltration into the vessels of target organs, such as the brain and kidney.…”
Section: Introductionmentioning
confidence: 99%